Direct tumor visual feedback during free breathing in 0.35T MRgRT. Issue 10 (15th September 2020) - Kim, Taeho; Lewis, Benjamin C.; Price, Alex; Mazur, Thomas; Gach, H. Michael; Park, Justin C.; Cai, Bin; Wittland, Erin; Henke, Lauren; Kim, Hyun; Mutic, Sasa; Green, Olga
Abstract: To present a tumor motion control system during free breathing using direct tumor visual feedback to patients in 0.35 T magnetic resonance‐guided radiotherapy (MRgRT). We present direct tumor visualization to patients by projecting real‐time cine MR images on an MR‐compatible display system inside a 0.35 T MRgRT bore. The direct tumor visualization included anatomical images with a target contour and an auto‐segmented gating contour. In addition, a beam‐status sign was added for patient guidance. The feasibility was investigated with a six‐patient clinical evaluation of the system in terms of tumor motion range and beam‐on time. Seven patients without visual guidance were used for comparison. Positions of the tumor and the auto‐segmented gating contour from the cine MR images were used in probability analysis to evaluate tumor motion control. In addition, beam‐on time was recorded to assess the efficacy of the visual feedback system. The direct tumor visualization system was developed and implemented in our clinic. The target contour extended 3 mm outside of the gating contour for 33.6 ± 24.9% of the time without visual guidance, and 37.2 ± 26.4% of the time with visual guidance. The average maximum motion outside of the gating contour was 14.4 ± 11.1 mm without and 13.0 ± 7.9 mm with visual guidance. Beam‐on time as a percentage was 43.9 ± 15.3% without visual guidance, and 48.0 ± 21.2% with visual guidance, but was not significantly different ( P = 0.34). We demonstrated the clinical feasibility and potential benefits of presenting direct tumor visual feedback to patients in MRgRT. The visual feedback allows patients to visualize and attempt to minimize tumor motion in free breathing. The proposed system and associated clinical workflow can be easily adapted for any type of MRgRT.